Simultaneous extraction-reaction process for biodiesel production from microalgae - Reem Shomal; Hiyam Hisham; Amal Mlhem; Rawan Hassan; Sulaiman Al-Zuhair (Energy Reports, 2019)
Biodiesel is a promising sustainable alternative to non-renewable petrodiesel. In this work, oils extracted from microalgae are used for biodiesel production. To simplify the process, the extraction of the oils and their reaction are made to take place simultaneously in one step. Immobilized lipase was used as the catalyst, and supercritical CO2 (SC-CO2) was used as an extraction solvent and reaction medium. The use of SC-CO2 allows easy separation of the products and leaves the leftover biomass uncontaminated, allowing it to be utilized in food and pharmaceutical applications. The effects of temperature (35-50~°C), reaction time (2-6 h), and methanol:oil (M:O) molar ratio (8:1-16:1) on biodiesel yield were investigated. Within 6 h, the maximum biodiesel production yield was found to be 19.3% at a temperature of 35~°C and at an M:O molar ratio of 8:1. The results hold promise in simplifying the microalgae-to-biodiesel production process.
Keywords: 330; Biodiesel; Extraction; Microalgae; Supercritical CO; Transesterification